Dental implant material related changes in molecular signatures in peri-implantitis – A systematic review and integrative analysis of omics in-vitro studies. Issue 1 (January 2023) - Freitag, Lena; Spinell, Thomas; Kröger, Annika; Würfl, Gregor; Lauseker, Michael; Hickel, Reinhard; Kebschull, Moritz
Abstract: Objective: Since peri-implantitis differs clinically and histopathologically from periodontitis, implant wear debris is considered to play a role in the destructive processes. This work aims to systematically review if titanium particles affect oral-related cells through changes in molecular signatures (e.g., transcriptome, proteome, epigenome), thereby promoting peri-implantitis. Methods: Leveraging three literature databases (Medline, Embase, Cochrane) a systematic search based on a priori defined PICOs was conducted: '-omics' studies examining titanium exposure in oral-related cells. After risk of bias assessments, lists of differentially expressed genes, proteins, and results of functional enrichment analyses were compiled. The significance of overlapping genes across multiple studies was assessed via Monte Carlo simulation and their ranking was verified using rank aggregation. Results: Out of 2104 screened articles we found 12 eligible publications. A significant overlap of gene expression in oral-related cells exposed to titanium particles was found in four studies. Furthermore, changes in biological processes like immune/inflammatory or stress response as well as toll-like receptor (TLR) and mitogen-activated protein kinase (MAPK) signaling pathways were linked to titanium in transcriptome and proteome studies. Epigenetic changes caused by titanium were detected but inconsistent. Conclusion: An influence of titanium implant wear debris on the development and progression of peri-implantitis is plausible but needs to be proven in further studies. Limitations arise from small sample sizes of included studies and insufficient publication of re-analyzable data.